Optimalisasi Peran Pembelajaran Bahasa dan Sastra Indonesia sebagai Wahana Pembentukan Karakter Peserta Didik dalam Menghadapi Masyarakat Ekonomi Asean (MEA) - Budhi Setiawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The effectuation of ASEAN Economic Community as of 2015 has demanded education institution to prepare qualified graduates equipped with various competencies according to their own fields of professionalism and expertise. In the ASEAN Economic Community era, each nation is predicted to tightly compete as to be a qualitatively and quantitatively prominent nation in its products either in the economic sector, in the cultural sector, or in the scientific and technological sector. It is necessary to be aware that the excellence or superiority of a nation is measured not only on the natural resources owned but also on the excellence of its human resources, in this case, namely: graduates of education institutions who are capable of encountering and dealing with all the future challenges promptly amid the very tight competition. To produce graduates with such profiles, at least a certain model of education is required, namely: the education model which is effectively able produce graduates bearing the expected characteristics. Similarly, the Indonesian language education shall be able to prepare learners with quality and excellence in the ASEAN Economic Community era. The learners (graduates) who are well-prepared to encounter ASEAN Economic Community shall bear the following: (1) in-depth mastery of science and technology (content); (2) good communication ability between the people; (3) high cognition or reliable intelligence; and (4) the characterization of national culture.